Development of a Home-Based Light Therapy for Fatigue Following Traumatic Brain Injury: Two Case Studies - Connolly, Laura J.; Ponsford, Jennie L.; Rajaratnam, Shantha M. W.; Lockley, Steven W. (Frontiers in Neurology, 2021)
Background and Objectives: Fatigue and sleep disturbance negatively impact quality of life following brain injury and there are no established treatments. Building on research showing efficacy of blue light therapy delivered via a lightbox in reducing fatigue and daytime sleepiness after traumatic brain injury (TBI), this paper describes the development and implementation of a novel in-home light therapy to alleviate fatigue and sleep disturbance in two case studies. Methods: During the 8-week lighting intervention, participants’ home lighting was adjusted to provide high intensity, blue-enriched (high melanopic) light all day as a stimulant and dimmer, blue-depleted (low melanopic) light for 3 hours before sleep as a soporific. The sham 8-week control condition resembled participants’ usual (baseline) lighting conditions (3000-4000K all day). Lighting conditions were crossed-over. Outcomes were measures of fatigue, subjective daytime sleepiness, sleep quality, insomnia symptoms, psychomotor vigilance and mood. Case study participants were a 35-year old male (5 years post-TBI), and a 46-year-old female (22 years post-TBI). Results: The relative proportion of melanopic lux was greater in Treatment lighting than Control during daytime, and lower during evenings. Participants found treatment to be feasible to implement, and was well-tolerated with no serious side effects noted. Self-reported compliance was >70%. Both cases demonstrated reduced fatigue, sleep disturbance and insomnia symptoms during the treatment lighting intervention. Case 2 additionally showed reductions in daytime sleepiness and depressive symptoms. As expected, symptoms trended towards baseline levels during the control condition. Discussion: Treatment was positively received and compliance rates were high, with no problematic side-effects. Participants expressed interest in continuing the ambient light therapy in their daily lives. Conclusions: These cases studies demonstrate the acceptability and feasibility of implementing a personalized in-home dynamic light treatment for TBI patients, with evidence for efficacy in reducing fatigue and sleep disturbance.